Dynamic Relationship between the Return of Gold, Crude Oil, and the Stock Exchange of Thailand Based on a Vector Autoregressive Model - Uthumrat, Wongtawan (International Journal of Energy Economics and Policy, 2022)
This research aims to investigate the dynamic relationship between the return of gold (RGOLD), crude oil (RCO), and the stock exchange of Thailand (RSET) using the Vector Autoregressive model: VAR(p) to analyze the secondary monthly data from January 2002 to October 2022. The paper reports three key findings. Firstly, the Granger causality test reveals two direct relationships: one between RCO and RSET, and the other between RSET, RCO, and RGOLD. Moreover, the researcher estimated the relationship between these variables by using the VAR(1) model. Secondly, the impulse response function (IRF) is applied by Granger causality results. When a variable is shocked by an impulse in the system, the RCO to RSET response increases by 0.21 percent, the RSET to RGOLD response increases by 0.10 percent, and the RCO to RGOLD response increases by 0.04 percent, before decreasing and approaching equilibrium. Finally, variance decomposition shows that the greatest portion of total variation in RGOLD, RCO, and RSET can be explained by itself in the long run. Moreover, the variation of RSET can be affected by the variation of RCO while the variation of RGOLD can be affected by the variation of RCO and RSET. Thus, investors, securities analysts, or fund managers can use the study’s results for strategic investment planning.